61 Penile Extra-Tunical Graft Reconstruction of Peyronie's Disease Concavity Deformities. Issue 1 (1st April 2022) - Diao, L; Badkhshan, S; VanDyke, M; Lewis, Z; Dropkin, B; Joice, G; Sanders, S; Hudak, S; Morey, A
ABSTRACT: Introduction: The extra-tunical grafting (ETG) procedure was recently introduced by UCSF investigators as a tunica-sparing technique for management of penile concavity deformities. Objective: We report our initial experience with the ETG procedure. Methods: We retrospectively reviewed clinical records of patients who underwent ETG at our tertiary-care referral center between 2017-2020. A collagen graft made from bovine pericardium (Lyoplant®) was placed overlying the defect without violating the tunica albuginea or mobilizing the neurovascular bundle. The stretched penile length (SPL) and circumference at the location of deformity were measured intra-operatively. Patient reported outcomes including overall satisfaction, graft palpability, and change in erectile function were evaluated by an anonymous ten-question online survey. Results: Nineteen men underwent ETG during the study period and had a median follow-up of 59 (IQR: 24 - 708) days. ETG was performed via either a window (15/19, 78.9%) or a de-gloving (4/19, 21.1%) incision with concomitant penile plication performed in 16/19 (84.2%) patients. Penile circumference increased by an average of 1.37 cm ± 0.53 (p = 0.03) at the location of deformity; pre- and post-operative SPL were similar (14.0 ± 1.4 vs. 14.0 ± 1.3 cm, p = 0.95). Fifteen patients (78.9%) responded to the online survey at an average of 240 days after surgery. Overall patient satisfaction was reported by 13/15 (86.7%) patients. Twelve out of 15 (80%) patients reported concavity deformity to be improved, with 73.3% reporting the deformity to be "much better" (Figure). One patient (5.3%) reported penile hypoesthesia/decrease in sensation. An improvement in erectile function was reported in 11/15 (73.3%) patients. Two of 15 (13.3%) patients noted no change in erectile function and 2/15 (13.3%) reported a decrease in erectile function. Of the 8 patients that had follow up greater than six months after surgery, graft palpability was reported in 4/8 (50%) patients but was not bothersome. Conclusions: The ETG procedure appears to be safe and effective for the treatment of penile concavity deformities. Patient outcomes and satisfaction are favorable at intermediate follow-up. Disclosure: Any of the authors act as a consultant, employee or shareholder of an industry for: Boston Scientific and Coloplast